Bending crashworthiness of bionic thin-walled structures inspired by sugar cane stalks. Issue 1 (1st December 2022) - Estrada, Q; Reynoso, E; Szwedowicz, D; Rodriguez-Mendez, A; Coutiño, E; Mora, T De la; Wiebe, L; Silva, J; Torres, C
Abstract: Recently, the design of biologically inspired thin-walled structures has been increasingly popular due to the successful adaptation of biological organisms to their environments due to millions of years of evolution. Plants with high bending resistance to counter the effect of wind forces on slender and tall stalks can be found in nature. To this end, this paper investigates the bending crashworthiness of mechanical structures inspired by sugar cane (Saccharum officinarum). The biological patterns of sugar cane were obtained with a Scanning Electron Microscope, and five bionic thin-walled structures (BTWS) were considered. In all cases, the structures were modeled with 6063-T5 aluminum and numerically evaluated using the finite element method using a three-point bending test. The effects of cross-section configuration on the crashworthiness performance of the structure were investigated. Our results show a better version of the BTWSs relative to a typical circular profile. An increase in energy absorption from 15.60% to 40.27% was computed. The best CFE performance was obtained for a structure defined by a central octagon surrounded by smaller trapeziums. Such a structure is therefore highly recommended for bending crashworthiness applications.